Developing an Android-Based LENTERA Application Media for Slow Learner Students at SMP Negeri 1 Geger - Heny Sulistyo Rini; Wiwik Widajati; Pamuji Pamuji (Universitas PGRI Madiun, 2025)
This study addressed the problem of giving students with learning disabilities access to useful learning materials. An interactive educational program called LENTERA (Learning Together for Special Needs) was created to help slow learners of the English language with concept comprehension, vocabulary acquisition, and memory consolidation. Concept, Design, Material Collection, Assembly, Testing, and Distribution were all included in the study, which used a development research approach based on the Multimedia Development Life Cycle (MDLC) model. Using Likert scale questionnaires given to practitioners, media experts, and material experts, feasibility and practicality were evaluated by experts. The results showed that practitioners (95.6%), media experts (94.67%), and material experts (95.29%) gave the application excellent feasibility ratings, suggesting that it has a great deal of friendly user as an instructional tool. Then, these findings imply that the LENTERA program has approved and usefulness for use in learning environments. By offering an approachable and captivating medium to support the special needs learning requirements of slow learners in acquiring English language abilities, the creation of this application makes a substantial addition to educational methods.